Lipophilicity evaluation of some thiazolyl‐1, 3, 4‐oxadiazole derivatives with antifungal activity. (2nd April 2018) - Stoica, Cristina Ioana; Ionuț, Ioana; Vlase, Laurian; Tiperciuc, Brîndușa; Marc, Gabriel; Oniga, Smaranda; Araniciu, Cătălin; Oniga, Ovidiu
Abstract: The chromatographic behavior of a series of thiazolyl‐1, 3, 4‐oxadiazoles with antifungal activity was studied by reverse‐phase thin‐layer chromatography (RP‐TLC). The lipophilicity parameters derived from RP‐TLC were correlated with the data derived from liquid‐chromatography mass‐spectrometry. Good linear relationships were observed between the chromatographic lipophilicity parameters and the theoretical lipophilicity descriptors (log P ) generated by various computer software and internet modules. Principal component analysis, applied on the experimental chromatographic lipophilicity indices and the theoretically calculated log P, enabled us to obtain a lipophilicity chart for better vizualization of the similarities and differences of the investigated compounds, which were grouped by k ‐means clustering in two congeneric classes.